Associations of PM2.5 exposure with diabetes-related mortality for California residents - Richy Zheng; Jason G. Su; Eahsan Shahriary; Sadeer Al-Kindi; Michael Jerrett; Timothy T. Brown; Rob McConnell; John Balmes (Frontiers in Public Health, 2026)
Background Emerging evidence links air pollution exposure to metabolic dysfunction; however, few studies have examined diabetes-related mortality in relation to ambient air pollutants using high-resolution exposure data at the population level. In the United States, particularly in large and geographically diverse states such as California, exposure contrasts and population heterogeneity provide an important setting to evaluate these associations. Methods We conducted a matched case–control analysis using California Department of Public Health (CDPH) Vital Records (2010–2021). Diabetes-related mortality events (ICD-10 E11) were identified as primary or contributory causes. Decedents (cases) were geocoded to residential addresses, and one-year rolling averages of fine particulate matter (PM 2.5 ) before death were assigned as individual exposures. Each death record was matched to its selected controls based on month and year of birth and race-ethnicity. Controls were identified from the same statewide CDPH mortality database and were eligible because they had not died by the corresponding case’s date of death. Because the number of eligible controls varied across matched strata, controls were randomly sampled within each matched stratum to achieve an overall control-to-case ratio of approximately 2:1 for the study population. The final dataset included 60,824 diabetes-related deaths and 119,053 controls. Exposures were standardized by their interquartile range (IQR) and conditional logistic regression models estimated associations between 1 year rolling average fine particulate matter (PM 2.5 ) exposure and odds of diabetes-related mortality, adjusting for age, sex, race-ethnicity, marital status, and education. Nitrogen dioxide (NO 2 ) was included as a co-pollutant for confounding control. Results PM 2.5 exposure (per 2.65 μg/m 3 IQR increase) was associated with a 18% higher odds of diabetes-related mortality (OR = 1.18; 95% CI: 1.15–1.22) before traffic indicator NO 2 adjustment and showed a stronger association with 21% higher odds (OR = 1.21; 95% CI: 1.17–1.25) after NO 2 adjustment. Health economics analysis estimated that reducing PM 2.5 exposure by its IQR could avoid losses of $31.2 million per 100,000 people. Conclusion Higher ambient PM 2.5 exposure was associated with increased odds of diabetes-related mortality in California even after adjustment for NO 2 and other impact factors. These findings support the need for continued strengthening of ambient air quality regulations.